Allamanda violacea Purple Allamanda - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document provides a detailed overview of the purple allamanda (Allamanda violacea), an evergreen vine or climbing shrub known for its two-toned reddish-purple to pink blooms. It describes the plant’s physical characteristics, growth habits, and uses in landscaping, such as covering arbors, walls, or as a hanging basket. The document also outlines the plant’s care requirements, including its preference for full sun, moderate drought tolerance, and need for nematode-free soil. Additionally, it highlights the plant’s non-native status, potential planting zones, and propagation methods. The purple allamanda is noted for its ornamental value and minimal pest issues, though all parts of the plant are poisonous. Original publication date September 1999.